Organizational development and natural resource management: evidence from central Honduras - Pender, John L.; Scherr, Sara J. (International Food Policy Research Institute, 1999)
The determinants of local organizational density and the impacts of local and external organizations on collective and private natural resource management decisions are investigated based on a survey of 48 villages in central Honduras. Factors positively associated with local organizational development include the presence of external organizations, population level, moderate population growth, lower population density, the presence of immigrants, distance from the urban market, literacy and coffee production. Local organizations are found to contribute to collective action to conserve resources, while government organizations appear to displace it, though not in all cases. The findings suggest that external organizations can play a catalytic role in fostering development of local organizations and emphasize the importance of improved understanding of the roles of local organizations, in order to enhance complementarity and minimize competition between these different agents in promoting sustainable development.